Indian women, myth and reality - Bagchi, Jasodhara (Hyderabad : Sangam Books : Distributed by Orient Longman, 1995)
Contributed seminar papers.
Includes bibliographical references and index.
Keywords: Women -- India; Women -- India -- Social conditions